Influence of process factors on surface measures on electrical discharge machined stainless steel using TOPSIS. (1st May 2019) - Huo, Jiaofei; Liu, Shoufa; Wang, Yinwei; Muthuramalingam, T; Ngoc Pi, Vu
Abstract: The optimal input process parameter combination has to be derived for obtaining the better multiple performance measures in any manufacturing process. An effort was attempted to perform multi criteria decision making for deriving surface performance measures in electrical discharge machining process using TOPSIS approach. It has been utilized to obtain minimum levels of multiple performance measures such as average white layer thickness and surface roughness with the maximum level of compressive residual stress while machining AISI 304 stainless steel using electrical discharge machining process. From the experimental investigation, it has been found that current due to plasma formation has most influent nature on performance measures. The optimal arrangement of machining process parameters has been found using TOPSIS based multi criteria decision making.